The Role of the Manado Police Criminal Investigation Unit in Suppressing Crimes Using Sharp Weapons - Valentin Vanny Lakidong; M. Syahrul Borman; Yoyok Ucok Suyono (Rechtsvinding, 2026)
Crimes involving the use of sharp weapons constitute a serious threat to public security and social order in urban areas. The widespread possession and misuse of sharp weapons have contributed to increasing levels of street crime, generating fear and insecurity within society. This study aims to analyze the role of the Criminal Investigation Unit (Satreskrim) of Manado City Police in suppressing crimes involving sharp weapons and to identify factors that hinder the effectiveness of its performance. This research employs an empirical juridical method, focusing on the implementation of normative legal provisions in real social conditions. Data were analyzed qualitatively through statutory review and field-based findings. The results indicate that Satreskrim Polresta Manado plays a strategic role as a law enforcement agency through preventive, repressive, and community-oriented measures, including patrols, investigations, and public engagement. However, the effectiveness of these efforts is constrained by limited personnel, insufficient technological support such as CCTV and information technology systems, and low public participation in providing information. The study concludes that strengthening human resources, technological infrastructure, and community cooperation is essential to enhance the effectiveness of law enforcement in suppressing crimes involving sharp weapons.